Electron-Positron Pair Production by Channeling Radiation inRadiator-Converter Approach: Computer Modeling; RREPS-13. Radiation from Relativistic Electrons in Periodic Structures and Meghri-13. Electron, Positron, Neutron and X-ray Scattering under External Influences - Abdrachitov S. V. Sergey Vladimirovich; Bogdanov O. V. Oleg Viktorovich; Dabagov S. B.; Pivovarov Yu. L. Yuriy Leonidovich; Tukhfatullin T. A. Timur Ahatovich (2013, 2013)
Title screen.